2018
DOI: 10.1016/j.brainres.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor modulation of dopamine release in the nucleus accumbens shell is unaffected by phencyclidine pretreatment: In vitro assessment using fast-scan cyclic voltammetry rat brain slices

Abstract: The non-competitive glutamate antagonist, phencyclidine is used in rodents to model behavioural deficits see in schizophrenia. Importantly, these deficits endure long after the cessation of short-term chronic treatment (sub-chronic), indicating that the drug treatment causes long-term changes in the physiology and/or chemistry of the brain. There is evidence that this may occur through glutamatergic modulation of mesolimbic dopamine release, perhaps involving metabotropic glutamate receptors (mGluR). This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Meanwhile, a widespread interaction between DA and GLU systems has been reported. A recent study showed that intraventricular injection of DA increased the GLU levels in the brain of rats using cerebral microdialysis,55 whereas glutamate antagonist (phencyclidine) caused schizophrenia-related behavioral deficits due to DA release 56. Our findings demonstrated that Tia treatment downregulated the level of GLU in TS rats, but whether it regulates the GLU system directly or influences the DA system to improve glutamate metabolism is a question that needs to be further verified.…”
Section: Discussionmentioning
confidence: 56%
“…Meanwhile, a widespread interaction between DA and GLU systems has been reported. A recent study showed that intraventricular injection of DA increased the GLU levels in the brain of rats using cerebral microdialysis,55 whereas glutamate antagonist (phencyclidine) caused schizophrenia-related behavioral deficits due to DA release 56. Our findings demonstrated that Tia treatment downregulated the level of GLU in TS rats, but whether it regulates the GLU system directly or influences the DA system to improve glutamate metabolism is a question that needs to be further verified.…”
Section: Discussionmentioning
confidence: 56%
“…We therefore sought to test the effect of PCP pretreatment, modeling schizophrenia on GABAergic control of dopamine release. Subchronic pretreatment with PCP, as used here, has been widely observed to cause behavioral changes resembling changes seen in schizophrenia (Cadinu et al., 2018; Javitt, 2007; Neill et al., 2010) and has been implemented as a relevant model for studying neurochemical and neurophysiological changes relevant to schizophrenia (Asif‐Malik et al., 2017; Gupta & Young, 2018; Yavas & Young, 2017, 2020). In slices taken from PCP‐pretreated rats, the level of stimulated release prior to acute drug infusion was similar to both non‐pretreated rats and saline‐pretreated rats, indicating that the pretreatment does not affect baseline stimulated release.…”
Section: Discussionmentioning
confidence: 99%
“…or saline (1 ml/kg, i.p.) twice daily (08:00 and 16:00) for 5 days, then left drug free in standard housing (as above) for at least 10 days, a procedure which produces reliable, long‐lasting behavioral changes resembling symptoms of schizophrenia (Grayson et al., 2007; Gupta & Young, 2018; Javitt, 2007; Neill et al., 2010). In each case, two saline pretreated and two PCP pretreated were housed together in the same cage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations